Evolution of two receptors detecting the same pheromone compound in crop pest moths of the genus Spodoptera - de Fouchier, Arthur; Sun, Xiao; Monsempes, Christelle; Mirabeau, Olivier; Jacquin-Joly, Emmanuelle; Montagné, Nicolas (Frontiers in Ecology and Evolution, 2015)
In moths, mate finding strongly rely on the detection of sex pheromones by pheromone receptors. Any modification in the functional properties of these receptors can have a drastic impact on reproduction. In the course of characterizing candidate pheromone receptors in the noctuid moth Spodoptera littoralis, we expressed them in Drosophila olfactory sensory neurons and stimulated them with a large panel of moth pheromone compounds. We found that two pheromone receptors detect (Z,E)-9,12-14:OAc, a minor component of the female pheromone blend. Whereas SlitOR6 is highly specific to this component, SlitOR13 is less sensitive and not strictly specific as it also detects (Z)9-14:OAc, another minor component of the sex pheromone. Interestingly, SlitOR13 expression is restricted to the distal part of male antennae, where we could identify a novel functional class of pheromone-sensitive neurons whose response spectrum matches that of SlitOR13. Based on a phylogenetic analysis of Lepidoptera pheromone receptors, we built an evolutionary scenario in which four different paralogous lineages emerged through gene duplications. The ability to bind (Z,E)-9,12-14:OAc appeared independently within three of these lineages, and an analysis of selective pressures revealed sites under positive selection that could have played a role in the emergence of functional properties of OR6 and OR13 in Spodoptera species.